The Effect of Digitization of Hospital Management Information Systems and Modernization of Information Technology on Patient Satisfaction Through the Perception of Digital Service Quality at Kaliwates General Hospital - Gilang Pradipta; Budi Santoso; Riyanto Setiawan Suharsono (Universitas KH. Abdul Chalim Mojokerto, 2026)
Kaliwates Hospital as a hospital faces the challenge of digital transformation to increase patient satisfaction amid a surge in polyclinic visits and the demand for fast services. This study examines the effect of digitalization of information system management and modernization of information technology on patient satisfaction with the quality of digital services as an intervening variable, as well as leadership development on employee performance through the same mediation. Using an explanatory design quantitative approach with a sample of 160 non-probability engineering patients and a saturated sample of employees, data were collected through a valid questionnaire (Cronbach α>0.8) and analyzed by SmartPLS-based Structural Equation Modeling (SEM). The results showed that the digitization of SIMRS had a positive effect on patient satisfaction through data integration and process automation; IT modernization is influential through WiFi-RME-telemedicine infrastructure; digital service quality (efficiency-privacy-promptness) mediates the relationship; Leadership Development improves employee performance through application efficiency and promptness of digital staff. The effect of partial mediation was confirmed to be moderate. The findings enrich the TAM-SDL theory in the context of East Java hospitals, recommending an integrated Digital Service Excellence Center Satu Sehat to optimize patient experience